EVALUATION OF PARKING AREA SPORT ACTIVITIES BASE ON LAND USE NEEDS EDUCATION ACTIVITIES SYSTEM - Akbardin, Juang (Journal of Architectural Research and Education, 2019)
The need for parking space in the land use system for educational activities is needed in line with the growth of vehicle users. Educational areas with a high center of activity really need adequate parking space for ease of accessibility. The center of sports activities in the area of higher education activities requires the ease of using vehicle parking. The system of sports activities in higher education areas with high movement activities requires evaluation of parking space requirements in accordance with the activity system. Analyzing parking space requirements based on system activities is the main objective of this study. Specifically the purpose of the study is based on the analysis of parking duration. The frequency and accumulation of vehicles in the parking area is a characteristic impact of the activity system of sports activities. The analysis method based on parking space units is analyzed based on parking methods with variables that affect vehicle use in the activity system in the sports activity zone. Variables of parking user characteristics are based on survey responses from vehicle users from their activity system. The results showed the existing conditions with 34 units of parking spaces with parking index 1.1764 with the need for parking space of 460 m2. With a system of high activity and vehicle growth, the parking area needs at the prediction of the next 10 years require an area of 59 parking spaces with a parking index of 0.949 with a parking area of 643.89 m2. So that the development of the parking area in the sports zone activity system requires an additional parking area of 183, 89 m2.